Aspectos fenológicos, ecológicos e de produtividade do Mapati (Pourouma cecropiifolia Mart.) - Falcão, Martha de Aguiar; Lleras, Eduardo (Acta Amazonica, 1980)
Data on the phenology, ecology and productivity of Mapati (Pourouma cecropiifolia Mart.) are presented here. In the Manaus region the species flowers at the height of the rainy season (April to June) with the crop at the and of the dry season and beginning of the next rainy season (October to January). Five species of insects were found visiting the flowers, of which four, all of them Apidae. had significant amounts of pollen. This suggests lack of pollination specificty. The number of flowers per tree varied between 4500 and 14000 for the five trees studied with a high fruit set (91%). A very high correlation was found between number of flowers and other production parameters such as number of green fruit (r = 0,999**), number of mature fruit (r = 0,999**) and crop weight (r = 0.988**). It is suggested that the number of flowers is intimately linked with the energetic capacity of the tree, and that the number of fruit reaching maturity is controlled endogenously in such a way as to maintain certain standards for individual fruit weight.